Kontribusi Pemikiran Partai Persatuan Pembangunan dalam Membangun Elektabilitas di Tengah Masyarakat Kabupaten Deli Serdang - yofi raja maulana; junaidi junaidi; aminuddin aminuddin (Jurnal Ragam Pengabdian, 2026)
This study examines the contribution of the United Development Party (PPP) in strengthening its electability among the people of Deli Serdang Regency. The research is important because political competition requires parties to continuously adapt their ideas, strategies, and programs to the changing needs of society. The study aims to analyze how PPP enhances its electability through political ideas, ideological values, and community-oriented strategies. A qualitative case study approach was employed. Data were collected through direct observation, in-depth interviews with party leaders, members, and local community representatives, as well as document analysis of party publications and related materials. The findings show that PPP strengthens its public appeal by promoting moderate Islamic values, supporting community economic empowerment, and emphasizing its historical role and ideological identity. The party also improves its electability through effective political communication, particularly by utilizing social media platforms and strengthening grassroots organizational networks. These strategies enable PPP to communicate its vision and programs more effectively while building closer relationships with voters. The study concludes that ideological strength alone is insufficient to increase electability. Political ideas must be translated into practical programs that respond to community needs and expectations. Therefore, political parties should continuously innovate, adapt to social and political changes, and strengthen public engagement to maintain trust, expand voter support, and improve long-term electoral performance.